2019
DOI: 10.1111/bjd.17624
|View full text |Cite
|
Sign up to set email alerts
|

Risankizumab vs. ustekinumab for plaque psoriasis: a critical appraisal

Abstract: Summary Aim Gordon et al. investigated the efficacy and safety of risankizumab [an anti‐interleukin (IL)‐23p19 biologic] compared with ustekinumab (anti‐IL‐12/23p40) and placebo in patients with moderate‐to‐severe chronic plaque psoriasis. This was a parallel‐group controlled study up to 16 weeks with a planned switch of the placebo group to risankizumab at 16 weeks. Setting and design This study consisted of two replicate phase III, double‐blinded randomized controlled trials (UltIMMa‐1 and UltIMMa‐2) conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Furthermore, the results of the UK study in 2019 showed that risankizumab had a higher efficacy than ustekinumab and a placebo for moderate to severe psoriasis. Moreover, adverse event profiles were similar among these groups [52].…”
Section: Future Perspectivesmentioning
confidence: 75%
“…Furthermore, the results of the UK study in 2019 showed that risankizumab had a higher efficacy than ustekinumab and a placebo for moderate to severe psoriasis. Moreover, adverse event profiles were similar among these groups [52].…”
Section: Future Perspectivesmentioning
confidence: 75%
“…The briakinumab and ustekinumab, anti-p40 antibodies that target both IL-12 and IL-23, were used to treat patients with severe psoriasis, but significantly increased the incidence of MACE [108][109][110]. In another study, risankizumab, a selective anti-IL23p19 antibody, however, did not increase adverse cardiovascular events in patients with moderate-to-severe chronic plaque psoriasis [111]. The discrepancies in these findings can be attributed to the complexity and inter-individual variations in the interactions between the IL22-IL23 pathways and the gut microbiota.…”
Section: Il-22 and Il-23 Signalingmentioning
confidence: 99%